2006
DOI: 10.1002/ajpa.20401
|View full text |Cite
|
Sign up to set email alerts
|

Continuity of interpersonal violence between Nubian communities

Abstract: Modern communities affiliated with the same culture have been shown to experience comparable levels of interpersonal violence, no matter what their size. It was hypothesized that a similar relationship would exist among ancient rural and urban people, but that accident-related trauma may be more prominent among rural dwellers due to their activity base. Through an analysis of antemortem trauma, this investigation contrasted the injury profile of Nubian adult villagers (N = 55) from the Kerma period (2500-1750 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
53
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 57 publications
(57 reference statements)
0
53
0
2
Order By: Relevance
“…In addition, from elsewhere in the world, several recent well-controlled studies showed a high prevalence of cranial vault trauma ranging from 8%-29% (Standen and Arriaza, 2000;Lessa and Mendonço de Souza, 2004;Judd, 2006;Torres-Rouff and Costa Junqueira, 2006;Tung, 2007).…”
Section: Discussion Craniofacial Injurymentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, from elsewhere in the world, several recent well-controlled studies showed a high prevalence of cranial vault trauma ranging from 8%-29% (Standen and Arriaza, 2000;Lessa and Mendonço de Souza, 2004;Judd, 2006;Torres-Rouff and Costa Junqueira, 2006;Tung, 2007).…”
Section: Discussion Craniofacial Injurymentioning
confidence: 98%
“…Several contributions have concentrated more specifically on probable evidence of interpersonal aggression (Walker, 1989;Smith, 1996Smith, , 1997Smith, , 2003Lambert, 1994Lambert, , 1997Jurmain and Bellifemine, 1997;Ogilvie and Hilton, 2000;Standen and Arriaza, 2000;Dawson et al, 2003;Willey and Emerson, 1993;Williamson et al, 2003;Lessa and Mendonça de Souza, 2004;Judd, 2006Judd, , 2008Roksandic et al, 2006;Torres-Rouff and Costa Junqueira, 2006;Buzon and Richman, 2007;Tung, 2007;Steadman, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This has been applied to skeletal studies investigating the rate, pattern of occurrence, level of risk (Lovejoy and Heiple, 1981), etiology of skeletal lesions and cultural and environmental context (Grauer and Roberts, 1996). Population-based research focusing on trauma in archeological populations has been conducted on a number of samples, for example, from Nubia (Alvrus, 1999;Buzon and Richman, 2007;Judd, 2006), Medieval England (Grauer and Roberts, 1996;Judd and Roberts, 1998), Chile (Standen and Arriaza, 2000), North America (Lovejoy and Heiple, 1981;Lambert, 1997;Jurmain, 2001), and Southeast Asia (Domett and Tayles, 2006). However, published data of trauma from past populations in the Pacific Islands are scarce or restricted to unpublished reports and descriptions within broader studies (e.g.…”
mentioning
confidence: 99%
“…As studies such as those carried out by Rösing [1990], Judd [2006] and others indicate that social class and occupation (subsistence related activities) will influence fracture frequencies and patterns, it was essential to ascertain that the two sites provided material from compatible societies with compatible social mix. Both written and archaeological sources give us a very clear picture of the medieval period in Ribe and Odense.…”
Section: Socio-economic MIX Of Skeletonsmentioning
confidence: 99%
“…This study correlates a measure of human sexual dimorphism with measures of frequencies, types and the distribution of skeletal traumas. Although the two osteological elements (human sexual dimorphism and fractures) have been studied separately by various scholars [Smith & Jones 1910;Nielsen 1970;McWhirr et al 1982;İşcan & Miller-Shaivitz 1984;Rösing 1990;İşcan et al 1994;Smith 1996;Steyn & İşcan 1997;González-Reimers et al 2000;Judd 2002aJudd ,b, 2004Judd , 2006Judd , 2008Rich et al 2005;Šlaus & Tomičic 2005], the correlation between the two types of data has, to the best of my knowledge, never been studied before, and has a potential which needs to be more widely acknowledged and explored. It is important to note that this study is focused on patterns of daily activity and the distribution of fractures between the two sexes, and not so much on individual cases and distribution of fractures between social classes.…”
mentioning
confidence: 99%